Characterization of 60 mm AlN Single Crystal Wafers Grown by the Physical Vapor Transport Method. Issue 16 (4th June 2019) - Wang, Qikun; Lei, Dan; He, Guangdong; Gong, Jianchao; Huang, Jiali; Wu, Jason
Abstract : Crack‐free bulk AlN single crystals up to 60 mm in diameter are successfully grown for the first time using a series of proprietary techniques by the physical vapor transport method. The single crystals are sliced into on‐axis (±0.2°) wafers and then lapped/polished following common wafering standards. The obtained wafers are characterized by Raman spectroscopy and high‐resolution X‐ray diffraction (HRXRD). The Raman spectra show an E2 (high) full width at half maximum (FWHM) of 2.85–2.87 cm −1 . The symmetric and asymmetric HRXRD rocking curves show FWHMs of 172–288 and 103–242 arcsec, respectively. The optical transmission spectra reveal that the entire wafers exhibit excellent ultraviolet (UV) transparency with absorption coefficients of 14–21 cm −1 in the UV range 4.43–4.77 eV (260–280 nm). The average etch pit density (EPD) determined by preferential chemical etching is about 2.3 × 10 5  cm −2 . The major impurities determined by evolved gas analysis and glow discharge mass spectrometry are carbon at 7.4 × 10 18  cm −3 (45 ppmw), oxygen at 1.2 × 10 19  cm −3 (100 ppmw), and silicon at 6.8 × 10 17  cm −3 (9.7 ppmw). The usable area of the 60 mm wafers exceeds 98%. Abstract : Crack‐free bulk AlN single crystals up to 60 mm in diameter are grown for the first time by the physical vapor transport method. The Raman spectra show an E2 (high) FWHM of 2.85–2.87 cm −1 . The entire wafers exhibit excellent UV transparency with absorption coefficients of 14–21 cm −1 in the range 4.43–4.77 eV.